A Phonological Description of the Local Dialect of Gomilica (SLA Data Point 392, OLA Data Point 21) - Gostenčnik, Januška; Kenda-Jež, Karmen (Jezikoslovni zapiski, 2023)
This article presents the local dialect of Gomilica (SLA T392), the Dolinsko variety of the Prekmurje dialect within the Pannonian dialect group (with some features of the Ravensko variety). It describes basic phonological and accentual features. The phonological description of the dialect is based on dialect material collected by Irena Lebar for the Slovenian Linguistic Atlas (SLA) in 1986. A comparison is made with all older transcriptions of this dialect (Ftičar 1957; Horvat 1963; Ftičar & Logar 1969–1971) and the phonological description for the Slavic Linguistic Atlas (OLA, Benedik 1981).